Analisis dan Rancang Bangun Sistem Informasi E-Commerce pada Usaha Mikro Kecil Menengah - Handayani, Sri Rizki; Setiawan, Dedy; Weni, Indra (Prodi Sistem Informasi FST Universitas Jambi, 2018)
Batik House Centre Dua Putri is a Small-Medium Micro Enterprise that engaged in Sales and Craftsmanship of Jambi’s Batik, Craftsmanship enterprise nowadays have faced a difficult time. Most of the Craftsman have difficulties in the marketing of the products because of the low demands. The Craftsman only works when there’s an Inquiry. These condition creates a lots of employee loss on most of the existed companies. This research aims to apply an E-commerce that can help promoting and raise the craftsman revenue and can help to give information and make it easier to buy products from Jambi’s Batik House dua putri for the consumers. System development method that used in this research is a DFD,ERD, and Flowchart. Software used for the development of the system is Adobe Dreamweaver and MySql as its database. This research creates an E-Commerce that hopefully can help and facilitate on promoting and sales. The system test results can be summed up that the system have worked Well.